Approach to the Fifth Five Year Plan of Assam - Planning Commission (Planning Commission, 1972)
Before considering as to what the approach of Assam to the Fifth Five Year Plan should be, it is necessary lo first have a look al the parameters which go into the making of its economy. The State consists of 8 plains districts—7 in Brahma-putra Valley and in Barak Valley—and 2 hill districts. The State covers an area of 78.5 thousand sq. kms. which accounts for 2.4 per cent of India's total area. The population of the State recorded an increase of 34.37 per cent in the decade 1961-71 over the 1961 population of 108 lakhs.
Government of Assam